Methane emission, intake, digestibility, performance and blood metabolites in sheep supplemented with cupuassu and tucuma cake in the eastern Amazon - Juliana Cristina de Castro Budel; Vinicius Costa Gomes de Castro; Shirley Motta de Souza; Benjamin de Souza Nahúm; Antônio Vinicius Corrêa Barbosa; Laurena Silva Rodrigues; Alexandre Berndt; Luciana Navajas Rennó; Eziquiel de Morais; Jamile Andrea Rodrigues da Silva; Thomaz Cyro Guimarães de Carvalho Rodrigues; André Guimarães Maciel e Silva; et al. (Frontiers in Veterinary Science, 2023)
The use of co-products as a feed supplement for ruminants makes livestock sustainable and optimizes the use of available areas and animal performance. Furthermore, when cakes are used, the residual fat composition can influence ruminal metabolism and methane (CH4) production. This study aimed to assess the effects of a diet containing cupuassu (CUP; Theobroma grandiflorum) and tucuma (TUC; Astrocaryum vulgare Mart.) cakes on intake, digestibility, serum metabolites, performance, and CH4 emissions in confined sheep in the Amazon. Approximately 28 animals, Dorper-Santa Inês, castrated, with an average initial live weight (ILW) of 35 ± 2.3 kg, were distributed in metabolic cages, in a completely randomized design, with four treatments and seven replications: (1) Control (C40), without the addition of Amazonian cake and with 40 g of ether extract (EE)/kg of dietary dry matter (DM); (2) CUP, the inclusion of the CUP cake and 70 g of EE/kg; (3) TUC, the inclusion of the TUC cake and 70 g of EE/kg; and (4) Control (C80), without the addition of Amazonian cake and with 80 g of EE/kg of dietary DM, with roughage to concentrate ratio of 40:60. The use of the TUC cake as a feed supplement reduced the intake of DM, crude protein (CP), and EE compared to the inclusion of the CUP cake (p < 0.05); however, it increased the intake of neutral detergent fiber (NDF) by 32% (p < 0.01). The highest averages of DM (732 g/kg) and CP (743 g/kg) digestibility were presented in C40, while the highest digestibility of NDF was presented in TUC (590 g/kg). Albumin levels stayed above and protein levels were below the reference values, and the C40 diet also obtained below results for cholesterol, triglycerides and High Density Lipoprotein (HDL) (P < 0.05). Sheep fed CUP (91 g) and TUC (45 g) had lower daily weight gains (DWGs) than those fed with diets without the inclusion of cakes (C40 = 119 g; C80 = 148 g), and feed efficiency (FE) was also lower in CUP (84) and TUC (60) diets than in C40 (119) and C80 (137) diets. CH4 emissions were lower in animals fed TUC (26 L/day) and higher in C40 (35 L/day); however, TUC resulted in higher CH4 emissions in grams/body live weight (BW) gain/day (353 g/BW/day) vs. 183 g/BW/day (C40), 157 g/BW/day (C80), and 221 g/BW/day (CUP). The supplementation with cakes did not improve intake, digestibility and performance, did not compromise blood metabolites and did not reduce the enteric CH4 emission in confined sheep in the Amazon; however, the use of CUP cake showed similar results to the control treatments and did not increase CH4 emissions, as occurred with the inclusion of TUC cake.